2023
DOI: 10.1093/ckj/sfad033
|View full text |Cite
|
Sign up to set email alerts
|

Expanded hemodialysis: what’s up, Doc?

Abstract: In the last years there has been an increasing interest in expanded hemodialysis (HDx), an emerging renal replacement therapy based on the use of medium cut off membranes (MCO). Thanks to the internal architecture of these type of membranes with a higher pore size and smaller fiber inner diameter to favour internal filtration rate they can increase the removal of larger middle molecules in conventional hemodialysis. Secondarily, several reports suggest that this therapy potentially improve the outcomes for end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…High cardiovascular morbidity and mortality, caused in part by chronic inflammation associated with endothelial dysfunction, remains a major challenge in the management of CKD and ESRD patients with underlying uremia and systemic microinflammation ( 8 12 ). Endothelial cells (ECs) - as a direct barrier to the uremic substances in the blood - are essential for maintaining vascular homeostasis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High cardiovascular morbidity and mortality, caused in part by chronic inflammation associated with endothelial dysfunction, remains a major challenge in the management of CKD and ESRD patients with underlying uremia and systemic microinflammation ( 8 12 ). Endothelial cells (ECs) - as a direct barrier to the uremic substances in the blood - are essential for maintaining vascular homeostasis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our prior results on the response of ECs to uremic microinflammation in the context of endothelial maladaptation ( 7 ). Linking the modulation of KLF2, a key vascular transcription factor, to this study provides further insight into the mechanisms underlying the beneficial effect of expanded hemodialysis with improved medium cut-off (MCO) dialyzers ( 8 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin E-coated membranes have also recently been used for expanded hemodialysis [39]. In a small prospective study, Maduell et al [40] found that the removal of medium-sized solutes, such as myoglobin, kappa-free immunoglobulin light chains, prolactin, and α1-microglobulin, in expanded hemodialysis with the vitamin E-coated membrane (Vie-18X, Asahi) was significantly higher than that in high-flux hemodialysis.…”
Section: Current State-of-the-art On the Use Of Commercial Vitamin E-...mentioning
confidence: 99%